O princípio da capacidade contributiva no âmbito das contribuições especiais - Frota, Rodrigo Antonio da Rocha (2006)
The present paper aims at the analysis of the country positive law, focusing in its base structure: the rules of law, as of its structure. This paper deals with the syntactic homogeneous feature of the positive law system and its relation to legal principles. Seeking, therefore, to verify the identity of such institutes, in order to, afterwards, concentrate efforts more specifically at the principle of contributive capacity and the relation to contributions. In this sense, the perspective by which the legal norm shall be analyzed corresponds to the Analytic-Constructivism theory, from Lourival Vilanova, taking into consideration the structure of rules and their order. To this angle of law study, we deem necessary to add a view from the perspective of Phenomenology, by the Value Theory, inherent to the law, due to its inseparable cultural characteristic. We conclude, finally, that the Contributive Capacity is a value of huge relevancy for the society that implanted it, ordering as in the form of rules, originating what we call Contributive Capacity Principle. The foregoing will be applied to nonobligatory tributes, among which are the Special Contributions, producing legal effects